Concepts of non-violence in the communities of the Fedoseevtsy Old Believers (based on a manuscript from the late 19th – early 20th century) - Pociechina, Helena (Papers in Linguistics, 2024)
The article compares the content of traditional religious prohibitions concerning the use of any type of aggression against one’s neighbour in the Old Believers’ environment with modern social standards of moral behaviour protected by law and understood as inalienable fundamental human rights. The study is based on the material excerpted from a manuscript from the collection of the former Monastery in Wojnowo, in Mazury (Poland). The selected manuscript consists of texts that served to perform the Orthodox rite of penance, therefore it contains several penance-related questions. Such questions about the committed sins asked by the confessor reminded the believers of what sins were. Apart from questions related strictly to religion, there were also those about community members’ norms of behaviour, which referred to prohibitions concerning certain behaviours and words regarding other community members. Such questions were repeated multiple times during every liturgical year during each penance and they shaped the believers’ concepts of family and social relations and served to improve their worldview. Aggression, expressed in the use of physical force and uttering swear words against family members, neighbours and even household animals, resulted in the need for penance to be imposed: from daily obeisance and strict fasting to the prohibition to participate in the life of the community. The texts from the manuscript describe various forms of punishment for each committed sinful act. The presented content exemplifies the normative-educational function of religious rites considered in the historical perspective.